(untitled) (Research, Society and Development, 2021)
Cell invasion mediated by angiotensin-converting enzyme 2 (ACE2) ectoenzyme and cellular proteases, such as trypsin-like proteases, cathepsins, transmembrane serine protease 2 and furin, target different tissues and organs as lung, gut, colon, ileum, kidney, gallbladder, heart muscle, epididymis, breast, ovary, stomach, bile duct, liver, oral cavity, lung, thyroid, esophagus, bladder, breast, uterus, prostate, pancreas, cerebellum, as well as calyx secreting cells in the nasal and sinus tissue. Loss of homeostasis of the renin-angiotensin system deregulates different axes compromising metabolic, cardiorespiratory, renal and hepatic control. SARS-CoV-2 infected cell undergoes pyroptosis and releases molecular patterns associated with damage: pro-inflammatory interleukin (IL) -1b, IL-6, IL-8, IL-10, IL-17, induced protein-10, interferon gamma, interferon gamma-induced protein-10, granulocyte colony-stimulating factor, granulocyte-macrophage colony-stimulating factor, macrophage inflammatory protein 1α and 1β, monocyte chemotherapy activating protein 1, inflammatory macrophage protein 1a, tumor necrosis-α, and mediators of immune-mediated inflammatory diseases. Cytokine storm and non-neutralizing antibodies produced by B cells circulate, cause/exacerbate damage to various organs. During viral replication and low oxygen saturation, loss of HIF-mediated cell homeostasis can lead to cell death/lysis and tissue damage, related to the hyperinflammatory response. The SARS-CoV-2-ACE2 can increase permeability, inflammation and microbial transmission by bacteremia or endotoxemia, in addition to dysbiosis. Thrombotic potential and the immunoinflammatory imbalance compromise function or lead to injuries and multiple organ failure. Infection by SARS-CoV-2 has the potential to modify the natural history of diseases, the relationships or interactions between the different systems and pathologies and the effects of their treatments, as in periodontal medicine approach.